Appearance and Existence in Mandarin Chinese - Zhang Niina Ning (Sciendo, 2019)
In Mandarin Chinese, the string of three overt elements in a row, a locative, a verb, and a nominal, asserts the existence of the entity denoted by the nominal in the location. This paper argues that the verb is contained in an adjunct, whereas the locative in its base position and the nominal establish a matrix predication relation. Thus, instead of the overt verb, the head of the matrix predicate of the construction is null. Moreover, a new analysis is provided to explain the obligatory argument sharing between the verb and the matrix predication of the construction. Furthermore, the paper argues that the agent of a transitive verb in certain types of embedded clauses needs to be Case-licensed by either the v of the selecting verb, as in an ECM construction, or a local c-commanding functional element, such as a complementizer, as in the English infinitive for construction. This Case-licensing explains why the transitive verb in the string has no agent. The research shows that the syntactic strategies to license abstract Cases in Chinese are similar to the ones found in other languages. Finally, the paper argues that the post-verbal -zhe is an adessive marker when it occurs in a non-progressive context.